EVALUATION OF INDEPENDENT FAMILY INDEX IN IBANGGA USING CONFIRMATORY FACTOR ANALYSIS: KENJERAN SUBDISTRICS, SURABAYA CASE STUDY - Ibad, Mursyidul; Firdausi, Haning; Lutfiya, Indah (Jurnal Biometrika dan Kependudukan, 2025)
The family is the smallest unit in society and plays an important role in shaping the quality of human resources. Family quality is measured through the Family Development Index (IBangga), which consists of the dimensions of harmony, independence, and happiness. Among these, the independence dimension has the lowest achievement. This study aims to analyze the influence of independence indicators on the independent family index in Kenjeran District, Surabaya City, considering that the independence dimension in this area remains relatively low. This research employed an analytical observational design with a cross-sectional approach. The sample included 108 families with couples of reproductive age, selected using stratified random sampling. Data collection was carried out using a questionnaire based on IBangga indicators, while data analysis utilized Confirmatory Factor Analysis (CFA) within the Structural Equation Modeling (SEM) framework using the AMOS application. The findings revealed that all indicators of family independence were statistically significant with a p-value of <0.001. Indicators with stronger influence included financial security, access to information, and family health, each showing factor loading values of ≥0.5. Conversely, indicators with relatively lower influence, but still contributing, were the fulfillment of basic needs and continuity of education, with factor loading values <0.3. Conclusion, efforts to strengthen family independence should focus on high-leverage indicators such as financial security, access to information, and family health. Nevertheless, indicators with lower leverage, including basic needs fulfillment and educational continuity, must not be overlooked, as they remain essential in supporting overall family independence.